Distribution and risk factors for childhood visual deficiency in Morocco: Case – control study - Loulidi Soukaina; Loukid Mohamed; Boussaa Samia (Clinical Epidemiology and Global Health)
Background: Visual impairment and blindness in children are a public health issue that needs to be addressed by health and government authorities. Our research aimed to identify the risk factors for childhood blindness and visual impairment in a region of Morocco. Methods: A case-control study was conducted in Marrakech-Safi region, in central Morocco, at the ophthalmology department of Errazi Hospital and in the diagnostic centre of Mohammed VI University Hospital Centre, as well as at the Abou El Abbas Sebti Institute for the Education of the Blind. 144 cases of visually impaired or blind children and 218 sighted control children from the same age group participated in the survey, which was carried out between November 2021 and October 2022 using the WHO/PBL questionnaire and analysed by SPSS 16.0. Results: The results showed the predominance of cataracts (43 %), followed by refractive error (26.4 %) and glaucoma (23.6 %). In youngsters, the primary cause of vision impairment is 63.2 % heredity. Thus, 50 % of children have a three-degree family history, with first-degree dominance accounting for 77.8 % of the total, and a significant association was detected for this variable (OR = 1.795, 95 % CI: 1.170–2.754). 60.4 % of children have ocular diseases from birth, and 24.3 % of parents were consanguineous marriages, however there was no significant association. Conclusion: Preventing visual abnormalities in children requires addressing the hereditary factor. Being the first of its kind in the area, our study's findings offer a valuable database for improved tracking of strategies used to prevent early blindness and visual impairment.